(untitled) (Plant Tissue Culture and Biotechnology, 2019)
Efficient micropropagation protocol was established in Cymbidium aloifolium through induction of secondary (2°) protocorms from primary (1°) protocorms, shoot buds (SBs) and protocorm-like bodies (PLBs) from pseudo-stem segments of in vitro raised seedlings. Neo-formation of 2° protocorms from 1° protocorms was obtained in liquid and agar-solidified Phytamax (PM) medium with NAA, 2,4-D, BAP and Kn at different concentrations and combinations. The highest number of 2° protocorms was induced in liquid PM medium (9.76 ± 0.88/1° protocorm) amended with 2.0 mg/l BAP + 1.0 mg/l 2,4- D. Although protocorms proliferated profusely in liquid medium, hyperhydricity was observed after prolonged culture. Both SBs and PLBs were induced from pseudo-stem segments on agar gelled PM medium and the mode of differentiation was dependent upon specific PGRs concentrations. The maximum number of SBs (5.80 ± 2.59/explant) was recorded in BAP and NAA at 1.0 mg/l each, while the maximum number of PLBs (7.20 ± 3.22/explant) were induced in 2.0 mg/l BAP and NAA each. Well developed root systems were induced SBs and PLBs on transferring to half-strength PM medium fortified with 0.5 mg/l IAA. The rooted plantlets were transferred to the greenhouse with 95% survival.